2021
DOI: 10.1177/10711007211017468
|View full text |Cite
|
Sign up to set email alerts
|

Low Rate of Peri-implant Osteolysis in Trabecular Metal Total Ankle Replacement on Short- to Midterm Follow-up

Abstract: Background: Peri-implant osteolysis is one of the major complications related to total ankle replacement. The aim of this study was to investigate the short- to midterm incidence of peri-implant osteolysis using computed tomography (CT) as imaging method for the Trabecular Metal Total Ankle (TMTA) implant representing a novel total ankle replacement (TAR) implant design regarding material and surgical technique. Methods: In total, 104 consecutive patients who had a primary TMTA replacement between March 2013 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Due to the small number of patients who underwent 5-year radiographic follow-up, the exact percentage of periprosthetic cyst development at 5 years for the entire study population could not be determined. However, a short-term to midterm follow-up study by Kormi et al 15 found a low osteolysis rate of 10% with this trabecular metal TAA system, which is actually much lower than those reported in midterm studies of other implants such as the Salto Talaris (21.2%) and INBONE II (18.2%). 1,4 The lower rate of cyst formation for the trabecular metal implant supports the idea that the use of this material may benefit overall osteointegration of the prosthesis, as previously discussed.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Due to the small number of patients who underwent 5-year radiographic follow-up, the exact percentage of periprosthetic cyst development at 5 years for the entire study population could not be determined. However, a short-term to midterm follow-up study by Kormi et al 15 found a low osteolysis rate of 10% with this trabecular metal TAA system, which is actually much lower than those reported in midterm studies of other implants such as the Salto Talaris (21.2%) and INBONE II (18.2%). 1,4 The lower rate of cyst formation for the trabecular metal implant supports the idea that the use of this material may benefit overall osteointegration of the prosthesis, as previously discussed.…”
Section: Discussionmentioning
confidence: 54%
“…Each average of the differences was superior to the previously published MCID. 2,15 As reported in Table 4 as well, for each individual component, more than 50% of patients were above the MCID. As seen in Figure 2, the postoperative outcomes seemed to plateau after 1 year, with a slight tendency for improvement.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…37 As with many TARs, survival rates diminish with longer follow-up. 4,5,19,25,32 However, similar to the AES prosthesis, results of the CCI compare unfavorably to other third-generation mobile- 7,18,21,28,30,37 and fixed-bearing implants 21 because of high complication rates and the formation of osteolytic cysts. 19,20,41 In our series, 45% of the reoperations performed were because of osteolytic cysts or loosening, which is comparable to other CCI studies.…”
Section: Discussionmentioning
confidence: 97%
“…The Zimmer TAR was selected because of a low rate of aseptic loosening of prosthetic components and functional outcomes noted by superior postoperative range of motion. 3,21 All surgeries were performed by a single fellowship-trained orthopaedic foot and ankle surgeon. Medical charts were reviewed to exclude patients who had died, were >95 years old, and/ or had comorbidities, including chronic pain, peripheral neuropathy, rheumatoid arthritis, stroke, muscular dystrophy, Charcot-Marie-Tooth disease, or a body mass index (BMI) of >40.…”
Section: Participant Recruitment and Screeningmentioning
confidence: 99%